Oferta y Turismo Gastronómico en la ciudad de Riobamba, provincia de Chimborazo. - Parra Velázquez, Ailen Elena (2023)
The city of Riobamba, capital of the province of Chimborazo is one of the first patrimonial cities, therefore, it keeps a lot of history, culture, tradition and gastronomy, the latter, over the years, has not been able to position itself within the country as an opportunity for economic and tourism growth for the territory. For this reason, the general objective of this research is to analyze the influence of the gastronomic tourism offer in the city of Riobamba, province of Chimborazo. The research was descriptive and correlational in nature, since details of the analysis are described and, in the same way, it is verified whether there is a relationship between one variable and the other. For this reason, bibliographic information was collected through articles, scientific journals and others, in order to serve as support for the development of this research, which made use of surveys aimed at two different types of public, on the one hand the inhabitants of the city and on the other the service providers/owners of food and beverage establishments, in order to inquire about the shortcomings or impediments that gastronomic tourism has had for its development in the city of Riobamba. Finally, based on the results of the surveys applied, it was found that among the shortcomings, the most important was the wrong use of food handling and hygiene, which triggers risks of disease to consumers and / or tourists. In addition, it was possible to verify the influence of the gastronomic offer and tourism in the city of Riobamba, confirming that the gastronomic offer has an impact on the development of gastronomic tourism. For this reason, a viable proposal was proposed to solve the problems found, which is to design a manual of food management and hygiene with a simple educational language capable of transmitting information to anyone, without being too invasive or with such extensive content, to encourage readers to investigate and apply the various processes and strategies, in order to promote gastronomic tourism in the city of Riobamba.